Proximate composition, functional and antimicrobial properties of wild harvest Terminalia carpentariae fruit - Zhang, J.; Phan, A.D.T.; Srivarathan, S.; Akter, S.; Sultanbawa, Y.; Cozzolino, D. (University of Jaffna, 2021)
Terminalia hadleyana (subsp. carpentariae C. T. White) is native to Northern Australia where fruits of this plant have been used as a traditional food by the Australian Indigenous people. The aim of this study was to evaluate the morphology, chemical composition, functional (e.g. vitamin C, phenolic content) and antimicrobial properties of T. carpentariae fruits, harvested from the wild at full maturity. Variability has been observed in both fruit morphology (size and weight) and chemical composition. Proximate analysis showed that these fruits have high concentration of dietary fibre (DF) (51.2 g/100 gDW), and minerals such as K (1780 mg/100 g DW), Ca (373 mg/100 g DW) and Mg (150 mg/100 g DW). High levels of total phenolic content (TPC) (11,392 mg GAE/100 g DW) and vitamin C (11,046 mg/100 g DW) were also observed. Fruit extracts also showed inhibitory effects against the growth of foodborne microorganisms such as Staphylococcus aureus, methicillin resistant Staphylococcus aureus, Pseudomonas aeruginosa and Shewanella putrefaciens. Overall, these results contribute to provide with relevant information of the potential of T. carpentariae fruit as a functional ingredient to the Australian Indigenous communities and the emerging Australian native food industry.
Keywords: Terminalia carpentariae; Phytochemicals; Hydrolysable tannins; Polyphenols; Antimicrobial activity; Antioxidant; Wild harvested